Hormonal therapy versus hysterectomy in the management of symptomatic adenomyosis - Parveen, Mehera; Zabin, Fahmida; Sultana, Nigar; Begum, Kazi F.; Ara, Rowson; Munmun, Salma A.; Wahid, Fatima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adenomyosis is a uterine disorder marked by symptoms such as pelvic pain, abnormal uterine bleeding (AUB), and infertility. The purpose of this study was to assess the effectiveness and patient outcomes of hormonal therapy versus hysterectomy in the management of symptomatic adenomyosis. The aim of this study was to evaluate the effectiveness and patient outcomes of hormonal therapy versus hysterectomy in the management of symptomatic adenomyosis. Methods: This prospective observational study included 85 patients with symptomatic adenomyosis treated with hormonal therapy (n=45) or hysterectomy (n=40) at Bangabandhu Sheikh Mujib Medical University (BSMMU) from 2022 to 2023. Inclusion criteria were adult females aged 20 years and above, while those with other gynecological disorders or severe comorbidities were excluded. Data on demographic characteristics, symptom relief, and patient satisfaction were analyzed using statistical package for the social sciences (SPSS) version 22.0, employing both descriptive and inferential statistics. Results: Most patients (n=85) were aged 40-49 years, with 55.6% receiving hormonal therapy. Hormonal therapy was used in 52.9% of cases, slightly surpassing hysterectomy at 47.1%. Treatment outcomes showed that 75.0% of hysterectomy patients experienced complete symptom relief, while only 44.4% in the hormonal therapy group reported the same, and 70.0% of hysterectomy patients were very satisfied compared to 33.3% in the hormonal therapy group. Hysterectomy patients had a shorter hospital stay, with 25.0% discharged within 2-3 days compared to 11.1% of hormonal therapy patients. Conclusions: Hysterectomy provides superior symptom relief and patient satisfaction compared to hormonal therapy in the management of symptomatic adenomyosis.